2015
DOI: 10.1089/pho.2014.3840
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Dental Enamel–Cavity Ablation Depth with Optimized Stepping Parameters Along the Focal Plane Normal Using a Three Axis, Numerically Controlled Picosecond Laser

Abstract: Objective: The purpose of this study was to establish a depth-control method in enamel-cavity ablation by optimizing the timing of the focal-plane-normal stepping and the single-step size of a three axis, numerically controlled picosecond laser. Background data: Although it has been proposed that picosecond lasers may be used to ablate dental hard tissue, the viability of such a depth-control method in enamel-cavity ablation remains uncertain. Methods: Forty-two enamel slices with approximately level surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Yuan et al conducted a preliminary study on the method of controlling the dentin depth error of a computerized, numerically controlled picosecond laser ablation. They found that the normal step size is positively correlated with the error of the ablation depth and the total depth-of-ablation error [ 32 ]. In the present study, we performed a single ablation of three layers using a single-layer ablation depth of 28 μm to reduce the error caused by multilayer ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al conducted a preliminary study on the method of controlling the dentin depth error of a computerized, numerically controlled picosecond laser ablation. They found that the normal step size is positively correlated with the error of the ablation depth and the total depth-of-ablation error [ 32 ]. In the present study, we performed a single ablation of three layers using a single-layer ablation depth of 28 μm to reduce the error caused by multilayer ablation.…”
Section: Discussionmentioning
confidence: 99%